2005
DOI: 10.1177/107602960501100211
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plasma Exchange in HELLP Syndrome

Abstract: Plasma exchange therapy has been successfully used in selected patients with hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome who have organ failure or refractory to treatment. There is no prospective study regarding plasma exchange and its effect in HELLP syndrome. The aim of this study was to investigate the effects of early postpartum use of plasma exchange in patients with HELLP syndrome on outcomes. The mortality rate and the recovery times were compared in patients with HELLP syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 17 publications
0
52
1
7
Order By: Relevance
“…Several case series suggest that the use of plasma exchange treatment may improve the outcome of both severe HELLP and AFLP. [58][59][60][61][62] …”
Section: What Is the Standard Management Of Thrombotic Microangiopathmentioning
confidence: 99%
“…Several case series suggest that the use of plasma exchange treatment may improve the outcome of both severe HELLP and AFLP. [58][59][60][61][62] …”
Section: What Is the Standard Management Of Thrombotic Microangiopathmentioning
confidence: 99%
“…The effectiveness of dexamethasone is not clearly defined [14]. However, some research demonstrated that postpartum plasma exchange therapy improves treatment outcomes in patients with severe HELLP syndrome [11,[15][16][17]. Patients who do not show improvement of platlets and ASAT levels within the first 24 to 48 hours after delivery and patients with renal or neurological involvement may have benefit from plasma-exchange between 24 and 72 hours postpartum as shown by Simetka et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…If the maternal or fetal conditions deteriorate, delivery should be performed as soon as possible. If the laboratory results or the clinical condition deteriorate, postpartum plasma exchange is reported to improve maternal outcome of severe HELLP syndrome [11].…”
Section: Introductionmentioning
confidence: 99%
“…24 The criteria for HELLP syndrome vary among studies, but generally include microangiopathic hemolytic anemia, increased AST more than 40-70 U/ml and thrombocytopenia with platelet counts less than 100, 000/µl. 28 , this approach was demonstrated to induce a rapid remission. For pregnancies fewer than 34 weeks gestation, where there is no maternal and fetal distress, glucocorticoids are recommended to accelerate fetal pulmonary maturity followed by delivery in 48 hours.…”
Section: Hellp (Hemolysis Elevated Liver Enzymes Low Platelets) Synmentioning
confidence: 99%